Leaf venation patterns in the genus Saxifraga (Saxifragaceae) - Zhang, Zhuoxin; Xia, Nianhe; Gornall, Richard J. (Phytotaxa, 2015)
Details of leaf venation in 150 species of Saxifraga L. representing all 13 sections are reported. Three main patterns were observed: palinactinodromous, acrodromous and camptodromous. Species with lobed leaves have palinactinodromous patterns, whereas those with entire leaves are acrodromous or camptodromous. Thus species from sections Heterisia, Irregulares, Cymbalaria, Cotylea and Mesogyne are palinactinodromous; species from sections Saxifraga, Ciliatae, Bronchiales and Trachyphyllum, in which some have lobed and some have entire leaves, are either palinactinodromous or acrodromous, according to the leaf margin; species from sections Ligulatae and Porphyrion, whose hydathodes secrete calcium bicarbonate, have camptodromous venation. Intermediate states occur in section Gymnopera (between palinactinodromous and camptodromous) and in section Porphyrion subsection Oppositifoliae and section Xanthizoon (intermediate between acrodromous and camptodromous). The pattern of distribution across the genus and selected outgroups shows that the ancestral state is likely to be palinactinodromous.